Romantika Sistem Bernegara dalam Wacana Keislaman - Yasin, Nur; Slamet, Slamet; Amina, Siti (Proceedings of Annual Conference for Muslim Scholars, 2022)
Islam is par excellence in its position as a resource of reference for every field of life. Islam provides regulatory guidelines starting from the smallest social level to the broadest scale, namely the state. The state as the largest social community has a great responsibility because it deals with the affairs of a large society. The Islamic state system had become a public discourse in the late twentieth and early twentieth centuries. The bearers of the ideology of the Islamic state display their ideas by including figures as legitimacy, including Sayyid Qutb and al-Mawdudi. His arguments are accompanied by the interpretation of the Qur'anic version of the characters' interpretations. In state theory, there are two forms of state, republic and monarchy. While the state system there are four kinds, namely nomocracy, democracy, aristocracy and theocracy. For the bearers of the ideology of the Islamic state, it is said that the Islamic state system has its own characteristics and is independent which is not the same as the theory of the state in general. The Islamic state aspires to form a supranational state that binds all state barriers so that there is no longer a state in the form of a national state. This discourse has become an endless debate. Some figures say that the supranational system is a utopian concept. With this debate, the Islamic state system becomes an unfinished romantic discourse.